Implementasi Manajemen Sarana dan Prasarana Pendidikan dalam Peningkatan Mutu Pembelajaran di SMAN Bareng Jombang - Qurrotul Ainiyah; Korida Husnaini (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2019)
Educational facilities and infrastructure are important factors in improving the efficiency of learning and learning. Management of educational facilities and infrastructure is defined as a collaborative process of the effective and efficient utilization of all educational facilities and infrastructure. The purpose of the management of educational facilities and infrastructure aims to provide professional services in the field of educational facilities and infrastructure in order to carry out the education process effectively and efficiently. This qualitative research aims to reveal the implementation of management of education facilities and infrastructure and the role of teachers in improving the quality of learning through the utilization of educational facilities and infrastructure at SMAN Bareng Jombang, by way of interviews, observation and documentation. The data validity technique uses triangulation so that the data obtained is more accurate.